Sphingolipidoses and Retinal Involvement: A Comprehensive Review - Chiara Carrozzi; Daniele Fumi; Davide Fasciolo; Federico Di Tizio; Serena Fragiotta; Mariachiara Di Pippo; Solmaz Abdolrahimzadeh (Applied Sciences)
Sphingolipidoses are a class of inherited lysosomal storage diseases, characterized by enzymatic deficiencies that impair sphingolipid degradation. This enzymatic malfunction results in the pathological accumulation of sphingolipids within lysosomes, leading to tissue damage across multiple organ systems. Among the various organs involved, the eye and particularly the retina, can be affected and this will be the primary focus of this study. This article will explore the various subtypes of sphingolipidoses, detailing their associated retinal abnormalities, with an emphasis on multimodal imaging findings and clinical recognition of these rare disorders.